Tax Planning Using Interest – An Organised Chaos for Those Interested - Legwaila, Thabo (Potchefstroom Electronic Law Journal, 2022)
Taxation of interest is one of the most complex areas of tax in South Africa. Various provisions apply to interest, with some regulating the inclusion of interest in gross income, others allowing for the deductibility of interest incurred, others limiting the amount of interest that is deductible and yet others providing for anti-avoidance tax measures using interest. This makes tax planning using interest to be a technically intense exercise, time consuming and often costly. This article critically analyses the provisions applicable to interest and highlights the circumstances in which they apply as well as the results of their application. It also illustrates instances of the overlaps in the application of these provisions.